2017
DOI: 10.1039/c7cc04021k
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of potent teixobactin analogues against methicillin-resistant Staphylococcus aureus (MRSA) through the replacement of l-allo-enduracididine with its isosteres

Abstract: We have synthesised 8 simplified, potent teixobactin analogues by replacing l-allo-enduracididine with its isosteres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…[24] As imilar result against MRSA ATCC 33591 has recently been observed by Singh and co-workers. [37] However, based on the MIC values, we observed that (Lys 10 )teixobactin was in fact consistently 2-fold less potent compared to (Arg 10 )teixobactin acrosst he S. aureus strainst ested;t he IC 50 data similarly reported a2 .2-fold loss of activity.B ecause (Arg 10 )teixobactin showed ab etter antibacterial profile here, Arg was maintained at this positioni nt he analogues 57-62 in our initial SAR study.…”
Section: Broth Microdilution and Growth Inhibition Assaysmentioning
confidence: 70%
See 3 more Smart Citations
“…[24] As imilar result against MRSA ATCC 33591 has recently been observed by Singh and co-workers. [37] However, based on the MIC values, we observed that (Lys 10 )teixobactin was in fact consistently 2-fold less potent compared to (Arg 10 )teixobactin acrosst he S. aureus strainst ested;t he IC 50 data similarly reported a2 .2-fold loss of activity.B ecause (Arg 10 )teixobactin showed ab etter antibacterial profile here, Arg was maintained at this positioni nt he analogues 57-62 in our initial SAR study.…”
Section: Broth Microdilution and Growth Inhibition Assaysmentioning
confidence: 70%
“…reported that (Lys 10 )teixobactin showed 2‐ to 4‐fold lower MIC values than (Arg 10 )teixobactin against specific strains of Staphylococcus epidermidis , Streptococcus salivarus , Enterococcus durans and Bacillus subtilis . A similar result against MRSA ATCC 33591 has recently been observed by Singh and co‐workers . However, based on the MIC values, we observed that (Lys 10 )teixobactin was in fact consistently 2‐fold less potent compared to (Arg 10 )teixobactin across the S. aureus strains tested; the IC 50 data similarly reported a 2.2‐fold loss of activity.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Teixobactin is an 11-amino acid “head to side-chain” cyclodepsipeptide ( Figure 1 ) with a D-Thr as a bridge head that forms the ester with the carboxylic group of a L-Ile. L-Ala and the post-translational modified L- allo- enduracidine (End), which contains a cyclic guanidine, are also part of the cycle ( Abdel Monaim et al, 2016a ; Dhara et al, 2016 ; Giltrap et al, 2016 ; Jin et al, 2016 , 2017 ; Yang et al, 2016 , 2017 ; Monaim et al, 2017 ; Parmar et al, 2017a , b ; Schumacher et al, 2017 ; Wu et al, 2017 ). The tail is formed by two moieties of L-Ser, two moieties of L-Ile, D- allo- Ile and D-Gln ending with a N- Me-D-Phe.…”
Section: Resultsmentioning
confidence: 99%